Advances in library administration and organization. Vol. 25 - Garten, Edward D. (Emerald, 2007)
This is ALAO's first nation specific volume. It represents part of an effort to further internationalize the journal's contents and interests. The volume's papers describe the Library & Information Science community in Finland, outline the history of Library & Information Science in the country and reviews the scientific achievements of its Library & Information Science scholars. These papers deal with some universal themes and topics in Library & Information Science research and practice and demonstrate the unique Library & Information Science contribution Finnish scholars/practitioners bring to these problems and issues. This book series is available electronically at website.
Includes index.
Keywords: Library administration.; elektronické knihy; electronic books